Communication and Subculture Identity: A Case Study of Transgender Students at a Waria (Transgender) Boarding School Al Fatah Yogyakarta - Maya Sandra Rosita Dewi (Department of Communications, Universitas Islam Indonesia, 2022)
Identity has a crucial role in the life of every individual in society. The identity inherent in a person makes it easier for them to understand hidden aspects of themselves. Communication is essential in forming one’s identity because identity consists of the meanings learned and projected to others through communication. Applying the symbolic interactionism perspective, which explains that individuals together with the surrounding community build and shape their world, which is composed of meaningful symbols, this study aims to find out how the role of communication in constructing identity as transgender students at a waria (transgender) boarding school Al-Fatah Yogyakarta. The study shows that transgender students at the Al-Fatah Transgender Islamic boarding school formed their contradictory and ambivalent identities as sinners, confident, polite, and calm. The transgender students expressed such ambivalent identity through two levels of verbal language, the Indonesian language as a general language and a set of unique internal community vocabularies. In addition, they also show up their identity through nonverbal channels, such as dress styles and visual attributes.